2014
DOI: 10.12980/apjtb.4.2014c75
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of polyphenolic–rich extract from Cola nitida (Kolanut) seed on key enzyme linked to type 2 diabetes and Fe2+ induced lipid peroxidation in rat pancreas in vitro

Abstract: This antioxidant and enzyme inhibition could be some of the possible mechanism by which C. nitida is use in folklore for the management/treatment of type-2 diabetes. However, the enzyme inhibitory properties of the extract could be attributed to the presence of catechin, epicatechin, apigenin and naringenin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…It has been cultivated in other parts of the World such as India, Australia, Malaysia, Trinidad, Jamaica, Brazil, and Hawaii [ 17 ]. Kola nut tree contains compounds that have antimicrobial [ 18 , 19 ], anti-inflammatory [ 20 ], antidiuretic [ 21 ], antidiabetic [ 22 ], antioxidative [ 23 ] and anticancer [ 24 ] activities. The plant has also been used to treat cardiovascular disease, whooping cough and asthma [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been cultivated in other parts of the World such as India, Australia, Malaysia, Trinidad, Jamaica, Brazil, and Hawaii [ 17 ]. Kola nut tree contains compounds that have antimicrobial [ 18 , 19 ], anti-inflammatory [ 20 ], antidiuretic [ 21 ], antidiabetic [ 22 ], antioxidative [ 23 ] and anticancer [ 24 ] activities. The plant has also been used to treat cardiovascular disease, whooping cough and asthma [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Take, for example, Frankenberger et al, 29 investigated the inhibitory effect of C. nitida on nitric oxide (NO) and tumour necrosis factor‐alpha (TNFα) released by lipopolysaccharide (LPS) activated. Oboh et al, 30 studied the inhibition of important type‐2 diabetes enzymes and the oxidative stress triggered by Fe 2+ in the pancreatic cells of an albino rat using C. nitida extracts. Momo et al, 31 reported the antioxidant activities and alpha‐amylase inhibition of aqueous C. nitida extracts.…”
Section: Resultsmentioning
confidence: 99%
“…All three studies by Tsujita et al, used porcine pancreatic α-amylases in addition to human α-amylases. 42,44,45 Additionally, 17 papers explicitly mentioned or referenced the utilisation of porcine pancreatic α-amylases 16,22,23,[25][26][27][34][35][36][37][38][39]41,43,48,50,52 (Table 2). Four studies indicated or referenced the use of α-amylases derived from a bacterial 24,31,47 or fungal source.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…25 In a separate investigation, the observed IC 50 value for kola nut was nearly ten-fold higher, though it is important to note that a positive control was not utilised so the reliability of the enzyme assay system cannot be ascertained. 38 In this systematic review, among the 17 studies that utilised porcine pancreatic α-amylase as the only enzyme, 16,22,23,[25][26][27][34][35][36][37][38][39]41,43,48,50,52 four of them specifically investigated the inhibitory potential of polyphenolic extracts from the edible parts of nuts belonging to the Anacardiaceae family, including pistachio (Pistacia vera), 36,37,48 and Atlantic terebinth (Pistacia terebinthus). 23 The Pistacia genus predominantly inhabits the northern hemisphere, encompasses both evergreen and deciduous varieties, and has long been recognised for medicinal properties.…”
Section: Inhibition Of Porcine Pancreatic and Non-mammalian α-Amylase...mentioning
confidence: 99%